Aging of lime-based TRM composites under natural environmental conditions - Esfahani, Ali Dalalbashi (2021)
Textile-reinforced mortar (TRM) composites, composed of textile fibers embedded in an inorganic matrix, have been found to be a sustainable solution for strengthening of existing masonry and concrete structures. Despite the extensive recent attention in understanding the mechanical performance of these composite, their long-term performance and durability remain basically unknown. To address this gap, this paper presents a comprehensive experimental and analytical study on the changes in the mechanical response of these composites across scales (from material characterization to bond and tensile tests of TRM composites) under indoor and outdoor conditions. For this purpose, steel and glass fibers with lime-based mortar are used to investigate the pull-out response and the tensile behavior of TRM composites. The results show that the long-term behavior of TRM composites for different ages is significantly dependent on the mortar and fiber combination and, therefore, can change notably between different TRM solutions. It is also observed that lime-based TRMs cannot reach their full mechanical properties under indoor conditions even after 3 years. Outdoor conditions lead to better curing of the samples and achieving significantly higher mechanical properties in these composites. However, it can also lead to a significant deterioration at later ages.